Interdigital Pilonidal Sinus: A Case Report - Savaş, Metin Deniz; Esgin, Mustafa (Fırat University, 2001)
In literature, interdigital pilonidal sinus cases are rarely seen and this disease is known as barber's disease. Here we present a case who worked as barber for 25 years, come with pilonidal sinus interdigital area and our surgical procedure.

Literatürde interdigital bölgede pilonidal sinüs vakası nadir görülmekle birlikte, berber hastalığı olarak bilinmektedir. Biz, 25 yıldır berberlik yapan ve ikinci interdigital bölgesinde pilonidal sinüs ile bize başvuran hastayı ve uyguladığımız cerrahi prosedürümüzü sunacağız.
ELDE İNTERDİGİTAL PİLONİDAL SİNUS:OLGU SUNUMU